Kesenian dalam Wacana Sejarah dan Peradaban Islam - M. Ma'ruf Misbah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
Art is the human creation as a part of civilization, Islamic arts as a brm of Muslim creativity belong tothe lslamic civilization, It has a very clase relation with the civilization it self and the Muslim creativity it has become a means of delivering messages in Islam as it had been done by Sunan Kalikaga and others.